Indian Forensic Science Research Literature: A Bibliometric Study of its Growth, Authorship and Publication Patterns - John Jeyasekar, J.; Saravanan, P. (Journal of Information and Knowledge, 2015)
A bibliometric analysis of the growth, authorship and publication patterns of forensic science literature for the period 2001 to 2013 was done using the data obtained from PubMed. MS-Excel worksheet was used for data analysis. The study revealed the exponential growth of forensic science literature. The relative growth rate fell from 0.83 in the year 2002 to 0.17 in the year 2013. The mean collaborative Index was 3.5; mean degree of collaboration was 0.89; mean collaborative coefficient was 0.6119 and mean modified collaborative coefficient was 0.6121 during the period of study. Forty one authors have contributed more than one percent of the total publication. Ten journals have contributed more than one percent of the total papers. Among these ’Journal of Forensic&Legal Medicine’ ranks first with 16.10% papers. Cluster map of co-words was also created using VOSviewer.